Selecting methods for water resources in coastal area: Comparative study cases of Hong Kong and Jakarta - Huwaina, Analissa; Koestoer, Raldi Hendrotoro Seputro (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Environmental problems in coastal areas are related to water resources. This is due to the high demand as a result of population activities on the coast beside the water quality on the coast is less good than that onthe mainland. The objective of this study is to review and compare the selection of clean water supply methods and their alternatives, especially in Hong Kong and Jakarta, from a public policy point of view. Hong Kong has a variety of water supply methods. Currently, the ones that are still used are seawater toilet flushing and water imports from China. In policy formation, Hong Kong has not looked at it holistically or is still traditional. In Indonesia, water resources are the obligation of the state to meet the needs of its population in accordance with the 1 945 Constitution. Jakarta's coastal areas have not fully experienced access to piped water to date, so the Provincial Government has chosen the method of providing water according to public acceptance.